Strategi Pemasaran HXCH Footwear Dalam Membangun Image Fashion Unisex di Instagram - Aldi Leo Faisal; Hendar Rubedo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
HXCH Footwear is a local sneaker and clothing brand from Bandung that has carried a unisex fashion concept since its establishment. Despite competitive product quality and pricing compared to similar local brands, HXCH Footwear has experienced declining purchase interest, particularly among female consumers. This study analyzes HXCH Footwear's marketing strategy, particularly promotion through Instagram, in building a unisex fashion image based on the marketing mix concept, identifies the obstacles faced; and formulates a marketing strategy based on SWOT analysis. This study uses a qualitative approach with a descriptive case study method. Data were obtained through in-depth interviews with the owner, social media manager, and consumers selected through purposive sampling, complemented by observation and documentation, then analyzed using the Miles and Huberman interactive model. Results show that the product, price, and place elements of the marketing mix were carefully designed to support the unisex concept, yet the promotion element suffers from dysfunction due to Instagram content dominated by male models, creating a gender bias in user image and contributing to a 31.2% sales decline among female consumers. The main obstacle stems from a limited gender perspective within the internal creative team. Based on SWOT analysis, strategies were formulated including involving female talent in the creative team, balanced cross-gender content scheduling, collaboration with female micro-influencers, and close-up video content production to highlight product quality.